Moral Issues and Christian Responses - Jung, L. Shannon (Loyle Shannon), 1943-; Jung, Patricia Beattie (Book collections on Project MUSE., 2013)
"This popular anthology for the study of Christian ethics, now in its eighth edition, has been a mainstay of undergraduate courses for nearly thirty years. Shannon and Patricia Jung provide an introduction to contemporary moral issues from decidedly, yet diverse, Christian moral perspectives. The anthology intentionally seeks a range of voices to produce a kind of 'point/counterpoint' discussion of an ethical issue. Issues include: the distinctiveness of Christian ethics, sexuality, reproductive rights, prejudice, immigration, the environment, economics, biomedical ethics, death and dying, terrorism, war, and globalization."--Publisher description.